Study on students' communication and interaction in collaborative learning processes with web-based social tools - Leow, Fui-Theng; Neo, Mai; Choon, Chang Yoong (Penerbit UTM Press, Universiti Teknologi Malaysia., 2014)
The rapid progression of ICT has influenced the social change and broadened the horizon of innovative learning which further enabled the web-based collaborative learning. Studies show that the use of web-based social tools is able to expand the social interaction and engagement among the students. In fact, many learning approaches in today’s higher education context have embedded collaborative learning activities. Therefore, it is important to investigate the student communicative acts and social interaction in the online communication process for sustaining and better supporting web-based collaborative learning. This study presents students’ feedback and their communicative acts in the process of collaborating on a multimedia project. Communicative Model of Collaborative Learning (CMCL) was used to analyze these inputs which obtained from open-ended questions, student interviews and students’ posting in social networking sites. The results showed that the CMCL was a useful tool for assessing the students’ social interaction and communicative acts in this learning approach. The outcomes of this study show that the use of CMCL is effective to analyze the student communication and interaction in web-based collaborative learning environments with more perspectives and reveal the impacts on student learning experience and attitudes.